Correlations of SELENOF and SELENOP genotypes with serum selenium levels and prostate cancer. Issue 4 (5th January 2018) - Ekoue, Dede N.; Ansong, Emmanuel; Liu, Li; Macias, Virgilia; Deaton, Ryan; Lacher, Craig; Picklo, Matthew; Nonn, Larisa; Gann, Peter H.; Kajdacsy‐Balla, Andre; Prins, Gail S.; Freeman, Vincent L.; et al.
Abstract : Background: Selenium status is inversely associated with the incidence of prostate cancer. However, supplementation trials have not indicated a benefit of selenium supplementation in reducing cancer risk. Polymorphisms in the gene encoding selenoprotein 15 (SELENOF) are associated with cancer incidence/mortality and present disproportionately in African Americans. Relationships among the genotype of selenoproteins implicated in increased cancer risk, selenium status, and race with prostate cancer were investigated. Methods: Tissue microarrays were used to assess SELENOF levels and cellular location in prostatic tissue. Sera and DNA from participants of the Chicago‐based Adiposity Study Cohort were used to quantify selenium levels and genotype frequencies of the genes for SELENOF and the selenium‐carrier protein selenoprotein P (SELENOP). Logistic regression models for dichotomous patient outcomes and regression models for continuous outcome were employed to identify both clinical, genetic, and biochemical characteristics that are associated with these outcomes. Results: SELENOF is dramatically reduced in prostate cancer and lower in tumors derived from African American men as compared to tumors obtained from Caucasians. Differing frequency of SELENOF polymorphisms and lower selenium levels were observed in African Americans as compared to Caucasians. SELENOF genotypes were associated with higher histological tumor grade. A polymorphism in SELENOP was associated with recurrence and higher serum PSA. Conclusions: These results indicate an interaction between selenium status and selenoprotein genotypes that may contribute to the disparity in prostate cancer incidence and outcome experienced by African Americans.